Considering the effective adoption of agricultural systems in the design of schemes for the promotion of tree cultivation, Costa Rica - Meza-Picado, Víctor (2024)
[Introduction]: The current cultivation of trees is insufficient to cover the national demand for wood, in this way small producers become an alternative solution to this situation, since despite having small areas, in the country there are abundant farms with these conditions; However, the current forest management scheme does not meet adequate standards for the incorporation of these small producers. [Objective]: To present an adaptive forest management scheme (AFMS) to the needs of the small farmer, in addition, to demonstrate the institutional availability to change according to expert criteria. [Methodology]: 1) the factors that influence the decision to adopt an agricultural or forestry production system were identified. 2) a profile of an ideal productive system that met the interests and preferences of the small producer was made, which was compared with the characteristics of agricultural and forestry production. 3) the proposal of an EMFA adjusted to the preferences and interest of the producer was made, which was also compared with the ideal profile. 4) three proposed change actions were presented to experts, obtaining different degrees of possibility of changes in the EMFA. [Results]: The discrepancy of the forest management scheme for the cultivation of trees with the perspective that a small producer has on an ideal production system was evidenced, as well as the substantial improvement that an EMFA would have in the valuation of the small producer and the institutional availability to change the EMFA according to the perspective of the small producers. [Conclusions]: The adjustment of the forest management scheme allows a greater adoption of the activity by the small producer, but it was recognized that any proposal that is made would be successful only if forest governance makes it more flexible and allows change.